Experimental Study on Oil Interruption Performance of Novel Cageless Angular Contact Ball Bearings - Tao Xu; Yanfu Li; Shuidian Xu; Jingyu Mo (Jixie chuandong)
The ability of bearings to resist oil interruption directly affects the reliability of aero engines. In order to explore the dry operation performance of a novel cageless angular contact ball bearing， an oil break test scheme under the bearing ring is designed， and a test platform and an operation program are constructed. The changes of bearing appearance， temperature， speed and current after oil cut off are analyzed. The results show that the dry running time of the new type of bearings is 51 min under high rotation speed and high axial load. It proves that the new type of bearings has good anti-oil interruption ability， and can be widely used in industry.